BIOAVAILABILITY OF CADMIUM IN SOILS, FERTILIZER SOURCES AND UPTAKE BY LEAFY VEGETABLES: A REVIEW - Onokebhagbe, V. O.; Adeleye, A. O.; Nkereuwen, M. E. (FUDMA Journal of Sciences, 2023)
Due to its ease of bioavailability and transfer within the terrestrial and aquatic environments, it has been widely established in the literature that cadmium is the most absorbed amongst the eight (8) heavy metals that are of scientific concern. This review documents the occurrences and sources of cadmium in soil, fertilizers, vegetables and industrial effluents that are invariably employed as fertilizer for agricultural use. Some research studies have indicated that vegetables have high absorption and accumulation of cadmium while its accumulation in grains is relatively low. Again, its presence in industrial effluent that is often discharged indiscriminately into the environment is equally documented. This current review equally spells out the ease of cadmium uptake in leafy vegetables and proliferation in human food chain, factors affecting its bioavailability in soils, documented toxic effects and symptoms. Numerous studies have shown that chronic exposure of humans through the food chain leads to a selective accumulation of cadmium in the liver and kidneys and in some studies, up to 75% of the total body burden was found in these organs. An understanding of cadmium sources and its occurrences in soils and uptake by vegetables is essential in establishing a framework for its risk assessment.
Keywords: Cadmium, Bioavailability, Soil, Vegetables, Fertilizer, Industrial effluent